Photoresponsive photoacid-macroion nano-assemblies - Zika, Alexander; Bernhardt, Sarah; Gröhn, Franziska (Polymers, 2020)
In this study, light-responsive nano-assemblies with light-switchable size based on photoacids are presented. Anionic disulfonated napthol derivates and cationic dendrimer macroions are used as building blocks for electrostatic self-assembly. Nanoparticles are already formed under the exclusion of light as a result of electrostatic interactions. Upon photoexcitation, an excited-state dissociation of the photoacidic hydroxyl group takes place, which leads to a more highly charged linker molecule and, subsequently, to a change in size and structure of the nano-assemblies. The effects of the charge ratio and the concentration on the stability have been examined with absorption spectroscopy and ζ-potential measurements. The influence of the chemical structure of three isomeric photoacids on the size and shape of the nanoscale aggregates has been studied by dynamic light scattering and atomic force microscopy, revealing a direct correlation of the strength of the photoacid with the changes of the assemblies upon irradiation.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Electrostatic self-assembly; Irradiation; Nano-assemblies; Nanostructures; Photoacid; Photoresponsive; Polyelectrolyte; Supramolecular; Switchability